Game-Based Learning for Improving Students’ Creative Thinking Skills in Science Learning: A Systematic Literature Review - I.M. Adi Kurniarta; I Wayan Redhana; I Nyoman Tika (Postgraduate, University of Mataram, 2025)
Science learning must be able to improve creative thinking skills to face the challenges of knowledge and technology development. This study aims to explore game-based learning models related to research trends, research designs used, fields of study that apply them, their influence on learning outcomes, and profiles of the use of game-based learning in science learning at various levels of education. This study is a Systematic Literature Review (SLR) with the PRISMA method to collect, analyze, and compile findings regarding game-based learning models in learning. This study is limited to articles obtained from the Publish or Perish search engine, from two databases, namely, Google Scholar and Crossref. The results of the literature review of 29 articles that met the inclusion criteria illustrate that game-based learning models make it easier for students to solve complex problems quickly, accurately, and efficiently using an innovative approach through a fun and challenging learning experience. The results of the literature review show that in the period 2020–2025, research on the application of game-based learning mostly uses the Research and Development method with the ADDIE model. The application of game-based learning in the field of science subjects is still very limited, namely only 14%, while the dominant application is in the field of mathematics. Game-based learning has a positive impact on students' cognitive, affective, and psychomotor learning outcomes, critical thinking skills, creativity, understanding of material, reading skills, learning motivation, science literacy, learning interest, physical activity, practical experience in dealing with emergencies, and building cooperation, communication, empathy, and social interaction. Game-based learning models can improve the quality of science learning.